Mechanical - thermal modelling and design of high-performance engineering structures - Aldabergen, Abilkhairkhan; Abdulov, Alen; Akzhigitov, Dulat; Srymbetov, Tamerlan (Nazarbayev University School of Engineering and Digital Sciences, 2019)
As the humanity continues and further accelerates the progress of technologies and structures of various fields, the integration of high-performance engineering structures has been an essential part in state-of-the-art engineering spheres. This work proposes the ways to design, examine, model and test such a structure: buckling-resistant pipes and structural members for nuclear reactors made from refractory alloys by means of powder metallurgy. Due to the complexity of the proposed system, the work was divided into corresponding work packages (see Appendices A - D), each presenting a detailed report and procedure with intermediate findings. The first two reports examine how the melting point of refractory metals is affected by the complex stress states; the third one studies a centrifugal sintering process; and the fourth work-package investigates the effect of the geometry on buckling. For each part, one student was assigned.
Keywords: complex stress states; melting; refractory materials; centrifugal sintering; buckling; high performance